2003
DOI: 10.1073/pnas.1231363100
|View full text |Cite
|
Sign up to set email alerts
|

CD40 ligand is a critical effector of Epstein–Barr virus in host cell survival and transformation

Abstract: Epstein-Barr virus (EBV),E pstein-Barr virus (EBV), a ubiquitous human lymphotropic herpesvirus, is a cause of lymphoproliferative diseases in immunosuppressed patients and infectious mononucleosis and is tightly associated with lymphoid malignancies such as Burkitt's lymphoma and T cell͞natural killer cell lymphoma (1). EBV infection is also associated with epithelial malignancies such as nasopharyngeal carcinoma and gastric carcinoma. An important biological property of EBV, which rationalizes its tight link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 29 publications
1
37
0
1
Order By: Relevance
“…Although LMP1 is thought to mimic the effect of constitutively active CD40 signaling, a previous in vitro study showed that WT EBV was not able to transform B cells obtained from patients with hyper-IgM syndrome, who have inactivating mutations of the gene encoding CD40L (37). Thus, expression of LMP1 as a result of EBV infection may not completely substitute for authentic CD40 signaling in B cells.…”
Section: Cd40-blocking Ab Inhibits Both Wt Ebv-and Lmp1-ko Ebv-inducementioning
confidence: 99%
“…Although LMP1 is thought to mimic the effect of constitutively active CD40 signaling, a previous in vitro study showed that WT EBV was not able to transform B cells obtained from patients with hyper-IgM syndrome, who have inactivating mutations of the gene encoding CD40L (37). Thus, expression of LMP1 as a result of EBV infection may not completely substitute for authentic CD40 signaling in B cells.…”
Section: Cd40-blocking Ab Inhibits Both Wt Ebv-and Lmp1-ko Ebv-inducementioning
confidence: 99%
“…CD40L is also expressed in EBV-infected B cells and plays a role in their in vitro transformation (12). To assess in vivo immunological function of CD40L on B cells, we established CD40L transgenic (CD40LTg) mice that constitutively express CD40L on B cells and demonstrated that CD40LTg mice spontaneously develop SLE-like autoimmune disease (13), suggesting that constitutive CD40L expression on B cells has a role in the development of SLE.…”
mentioning
confidence: 99%
“…(sense) and 5?-GGG ACC ACA GAC AAC ATC AG-3? (antisense), were used [12] . The PCR condition was 30 cycles consisting of denaturation for 30 s at 94°C, annealing for 30 s at 58°C and extension for 1 min at 72°C.…”
Section: Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%
“…CD40 or CD40L mutated mice had showed severe defects in the establishment of B cell memory and very few LCLs from XHIM B cells upon EBV infection were observed [7,10 . It was found that EBV infection of B cells induces ectopic expression of CD40L 12 and it's expression could stimulate CD40-mediated growth signals in B cells 10,13,14 , suggesting that EBV-induced CD40L facilitates B cell proliferation. The CD40L expression on LCLs and the other EBV-positive B cell lines suggests longterm expression of EBV-induced CD40L.…”
Section: Introductionmentioning
confidence: 99%